2014
DOI: 10.1111/bcp.12469
|View full text |Cite
|
Sign up to set email alerts
|

Effects of factor Xa on the expression of proteins in femoral arteries from type 2 diabetic patients

Abstract: AIMFurther to its pivotal role in haemostasis, factor Xa (FXa) promotes effects on the vascular wall. The purpose of the study was to evaluate if FXa modifies the expression level of energy metabolism and oxidative stress-related proteins in femoral arteries obtained from type 2 diabetic patients with end-stage vasculopathy. METHODSFemoral arteries were obtained from 12 type 2 diabetic patients who underwent leg amputation. Segments from the femoral arteries were incubated in vitro alone and in the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…40 In our studies, Noxs mRNA expressions were not altered among Figure IV in the online-only Data Supplement), which is consistent with our previous finding that exacerbation of DN in the absence of eNOS is not associated with oxidative stress marker (reduced and oxidized glutathiones). 6 NADPH oxidases or oxidative stress dose not cause injurious effects in our model.…”
Section: Discussionsupporting
confidence: 92%
“…40 In our studies, Noxs mRNA expressions were not altered among Figure IV in the online-only Data Supplement), which is consistent with our previous finding that exacerbation of DN in the absence of eNOS is not associated with oxidative stress marker (reduced and oxidized glutathiones). 6 NADPH oxidases or oxidative stress dose not cause injurious effects in our model.…”
Section: Discussionsupporting
confidence: 92%
“…The fact that in supernatants from AAA explants, IL-10 production was not modified with respect to control while in rivaroxaban-incubated AAA was significantly increased might suggest an independent effect of rivaroxaban on endogenous FXa. In this regard, in a previous study performed in femoral arteries of diabetic patients, we have also observed an effect of rivaroxaban probably unrelated to FXa on the expression of long mitochondrial fatty acid transporters [25]. As we mentioned in that report, it is known the existence of rivaroxaban-derived metabolites and, therefore, we cannot rule out that some of the apparently FXa-independent effects of rivaroxaban could be attributed to such metabolites [48].…”
Section: Discussionmentioning
confidence: 65%
“…At the AAA site, the FXa inhibitor, rivaroxaban, significantly reduced the expression level of the gp67-and 91-phox NADPH oxidase isotypes, suggesting the involvement of FXa in such increased expression. Accordingly, in femoral arteries obtained from diabetic patients we have also demonstrated that rivaroxaban reduced the expression of oxidative stressrelated proteins [25] . Interestingly, it was suggested that NOS2, whose expression was significantly reduced by rivaroxaban in the AAA site, might be link between inflammation and oxidative stress in AAA since NOS2 was also demonstrated as primary sources of superoxide anion in AAA [50].…”
Section: Effects Of Rivaroxaban On the Expression Levels Of Oxidativementioning
confidence: 67%
See 1 more Smart Citation
“…Thrombin-PAR-1 interaction activates the signaling axis involved in actinic cytoskeleton modifications of endothelial cells, thus contributing to endothelial barrier disruption and increased permeability [5]. In patients suffering from vascular disease, factor Xa modifies the expression levels of oxidative stress-induced proteins, thereby affecting aerobic mitochondrial metabolism [6]. Through the stimulation of PAR-1 and -2 and the activation of insulin-like growth factor binding protein 5 (IGFBP5) and p53, factor Xa induces a senescent phenotype and the expression of pro-inflammatory molecules in the smooth muscle cells of the vascular wall [7].…”
Section: Introductionmentioning
confidence: 99%